Workplace deviant behaviour : does psychological contract violation matter? An empirical evidence / Abdul Rahman Abdul Rahim and Aizzat Mohd. Nasurdin - Abdul Rahim, Abdul Rahman; Mohd. Nasurdin, Aizzat (Research Management Institute (RMI), 2011)
Workplace deviant behaviour refers to "the voluntary behaviour that violates significant organizational norms". In this study, 355 manufacturing industry employees participated in an investigation into the impact of Psychological Contract Violation (PCV) on Workplace Deviant Behaviour (WDB). Three forms of deviant behaviour were identified: interpersonal deviance, production deviance, and property deviance. Further to this three PCV dimensions were also identified, namely, growth and development, autonomy and organizational support. The regression analyses performed yielded mixed results. PCV with respect to 'autonomy and control' demonstrated a negative relationship with interpersonal deviance and property deviance, but a positive relationship with production deviance. PCV with regard to 'growth and development' was found to exhibit a negative relationship with interpersonal deviance, but a positive relationship with property deviance. 'Organizational support' PCV exhibited no significant relationship with WDB.